ANALISIS ARUS KAS OPERASI DAN RETURN ON ASSET (ROA) TERHADAP RETURN SAHAM DENGAN LABA AKUNTANSI SEBAGAI VARIABEL MODERASI - Wulandari, Retno (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
This study aims to examine the effect of operating cash flow and return on assets on stock returns with accounting profit as a moderating variable. The sample technique used purposive sampling on LQ 45 listed companies (IDX) for the period 2016-2018, because the samples were taken using certain criteria and obtained 20 companies as research samples. The data analysis method is multiple liner regression analysis. The result of the research shows that operating cash flow has a negative effect on stock returns, ROA negatively affects stock returns, and then accounting profit affects stock returns. Associated with path analysis, the results are obtained, firstly accounting profit weakens the relationship between cash flow and stock returns and secondly, accounting profit strengthens the relationship between ROA on stock returns.